ANALYSIS OF HOTS INDICATOR ON SENIOR HIGH SCHOOLS PHYSICS EXAM QUESTION IN WETS PASAMAN DISTRICT - Sonia Nur Riza; Yenni Darvina; Silvi Yulia Sari; Fanny Rahmatina Rahim (Universitas Negeri Padang, 2021)
Education is a fundamental foundation for human life. In every educational development, there is always a change in the curriculum. The 2013 curriculum requires HOTS-based learning. In the 2013 curriculum, students must practice thinking skills at the HOTS level by giving HOTS questions. Because, the teacher must provide students with HOTS questions. The observations show that the questions used in Senior High Schools throughout West Pasaman District are still in the low category and do not meet the excellent proportion of questions. Therefore, an indicator analysis research was carried out on Physics questions for SMAN in West Pasaman District. This research includes descriptive research is includes in the qualitative approach. With population of this research is about Midterm Exam and Semester Exam Senior High Schools in 2018/2019 and 2019/2020 in semesters 1 and 2 in West Pasaman District. The research data was taken using an analytical instrument of question presentation and data collection with proof of questions. From the research has been done, it was found that the questions that have the highest availability of HOTS indicators for Semester Exam between 2018/2019 and 2019/2020 are in class XI and XII Semester Exam in 2018/2019 while in class X, namely in 2019/2020. As for the Midterm Exam in using the HOTS questions, the highest is Senior High School 1 Pasaman, and the lowest is Senior High School 1 Gunung Tuleh. Based on the research that has been done, it is found that these questions do not meet the availability of HOTS questions.